Assessing the impact of China’s river chief system on enterprise pollution discharge - Du, Jianxiao; Li, Bo (Frontiers in Public Health, 2023)
The River Chief System (RCS), a pivotal environmental governance policy promoted by the Chinese government, has far-reaching implications for public health. This study aims to comprehensively assess the impact of RCS on corporate pollution emissions, emphasizing its role in improving environmental quality and safeguarding public health. Utilizing a database of industrial enterprises and data from heavily polluting enterprises spanning 2003 to 2013. Manual collation of RCS policy implementation across prefecture-level cities during the same period. Application of the DID method to verify the impact of RCS on the extent of corporate pollution emissions. RCS significantly reduces pollution emissions from enterprises. Heterogeneity analysis reveals RCS to be more effective in addressing visible pollutants in rivers, non-provincial capitals, and heavily polluting industries, resulting in a notable reduction in pollution emissions. Mechanism testing underscores the importance of increasing government attention to environmental protection and strengthening environmental regulation as key factors contributing to RCS’s success in reducing pollution emissions from enterprises. Additionally, the study finds that improving the business environment of enterprises, measured through the marketization index, enhances the effectiveness of RCS in improving river pollution by enterprises. This study introduces a new perspective on examining the pollution reduction and abatement effects of RCS, addressing a gap in micro-level research. The findings not only contribute to the understanding of RCS’s impact on pollution but also offer valuable insights for governments and policymakers in promoting the further development and implementation of RCS policies. The results of this research are of significant importance in strengthening environmental governance and safeguarding public health. By effectively controlling corporate pollution emissions, RCS contributes positively to improving environmental quality and, consequently, enhancing public health outcomes.